1988
DOI: 10.1002/cjce.5450660516
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and selectivity of reactions of 1‐alkenes on HY zeolite: The influence of chain length

Abstract: Catalytic reactions of 1‐alkenes on HY have been studied at 400°C. Skeletal isomerization to the corresponding rnonornethylalkene is the dominant initial process. Cracking and coke formation are also observed as initial processes. Initial cracking selectivity can be accounted for by monomolecular β‐scission processes involving a carbenium ion intermediate. However, the initial cracking product distribution for l‐hexene must be explained by assuming some contribution from a dimerization‐cracking mechanism. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…14 belong to family 5; steps 7 and 10 belong to family 6; step 12 belongs to family 7; and steps 5 and 8 belong to family 9. Our experimental data (Yaluris et al, 1994a) and results presented by other workers (Abbot and Wojciechowski, 1988b;Corma et al, 1985;Kramer et al, 1985;McVicker et al, 1983;Ono and Kanae, 1991;Shertukde et al, 1992;Shigeishi et al, 1991) indicate that isomerization and desorption processes are equilibrated at the reaction conditions employed here. Therefore, we set the Evans-Polanyi constants of families 4 and 5 to zero.…”
Section: Isobutane Crackingsupporting
confidence: 77%
“…14 belong to family 5; steps 7 and 10 belong to family 6; step 12 belongs to family 7; and steps 5 and 8 belong to family 9. Our experimental data (Yaluris et al, 1994a) and results presented by other workers (Abbot and Wojciechowski, 1988b;Corma et al, 1985;Kramer et al, 1985;McVicker et al, 1983;Ono and Kanae, 1991;Shertukde et al, 1992;Shigeishi et al, 1991) indicate that isomerization and desorption processes are equilibrated at the reaction conditions employed here. Therefore, we set the Evans-Polanyi constants of families 4 and 5 to zero.…”
Section: Isobutane Crackingsupporting
confidence: 77%
“…12,13 Experimentally, it is usually found that the C 1 and C 2 product selectivities deviate from the ASF distribution. 12,[14][15][16][17][18][19][20] Two important schools of thought exist about the nature of the catalytically active surface. On the one hand, it is assumed that the close-packed surfaces (terraces) are the active sites.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed route depends on the catalyst 41 acidity and molecular size of the carbenium ion [9,[13][14][15][16]. Most of 42 the research interests involving olefins interconversion kinetics 43 focus on two separate fields: one is the transformation of light 44 olefins (C 2 -C 4 ) [17][18][19] for the Methanol-to-Olefins (MTO) process, 45 where C 2 -C 3 are the dominant products [20][21][22][23][24]; the other is the 46 conversion of higher olefins [25,26] for the Fluidized Catalytic 47 Cracking (FCC) process, where C 5 -C 8 olefins are produced and 48 undergo further cracking. Neither covers full C 2 -C 7 range of the 49 MTP process.…”
mentioning
confidence: 99%